2009
DOI: 10.1186/1476-4598-8-79
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and identification of potential biomarkers of papillary thyroid carcinoma

Abstract: Background: Thyroid carcinoma is the most common endocrine malignancy and a common cancer among the malignancies of head and neck. Noninvasive and convenient biomarkers for diagnosis of papillary thyroid carcinoma (PTC) as early as possible remain an urgent need. The aim of this study was to discover and identify potential protein biomarkers for PTC specifically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 23 publications
(15 reference statements)
1
64
0
1
Order By: Relevance
“…Consistent with these findings, APOC1 has been reported to be a promising serum marker for the diagnosis and treatment of multiple cancers, such as gastric cancer,25 pancreatic cancer,26 colorectal cancer,27 thyroid carcinoma,28 and non‐small cell lung cancer 29…”
Section: Discussionsupporting
confidence: 55%
“…Consistent with these findings, APOC1 has been reported to be a promising serum marker for the diagnosis and treatment of multiple cancers, such as gastric cancer,25 pancreatic cancer,26 colorectal cancer,27 thyroid carcinoma,28 and non‐small cell lung cancer 29…”
Section: Discussionsupporting
confidence: 55%
“…Apolipoprotein C-III-containing HDL may play a key role in the prevention of apolipoprotein C-III-induced hypertriglyceridemia (30). Recently, SELDI-TOF (surface-enhanced laser desorption ionization time of flight) analysis suggests a link between an ion species at m∕z 8,697 of apolipoprotein C-III and papillary thyroid carcinoma (31). However, SELDI-TOF is a low-resolution technique, requires off-line LC purification, and has shown limited utility in biomarker development (32).…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 3972 Da was compared to the identified ITIH4 by Villanueva et al and found to be increased in the sera of prostate and bladder cancer patients (27). Protein peaks at 6630 and 6629 Da were identified as apolipoprotein C-I in the sera of patients with papillary thyroid carcinoma by Fan et al (28) and sera of colorectal cancer patients by Ward et al (29). The peak at 6429 Da has not yet been identified but was described as a putative biomarker in lung cancer by Yang et al (30).…”
Section: Discussionmentioning
confidence: 99%